divide the sum of -3/4 and 5/9 by their difference
Answers
Answered by
8
sum of numbers
-3/4+5/9
=-3*9+5*4/9*4
=-27+20/36
=-7/36
difference of numbers
-3/4-5/9
=-3*9-5*4/9*4
=-27-20/36
=-47/36
According to the question
-7/36÷-47/36
=-7/36 x -36/47
=7/47
-3/4+5/9
=-3*9+5*4/9*4
=-27+20/36
=-7/36
difference of numbers
-3/4-5/9
=-3*9-5*4/9*4
=-27-20/36
=-47/36
According to the question
-7/36÷-47/36
=-7/36 x -36/47
=7/47
Answered by
2
Step-by-step explanation:
plz like & comments
mark me as a BRAINLIST
Attachments:
![](https://hi-static.z-dn.net/files/d98/c859e762856ee8484a8bc220e49afdda.jpg)
Similar questions